Identification of the RcWRKY family in Rubus chingii and analysis of its regulatory mechanisms for flavonoid synthesis - Xu, XiuRong; Cheng, Yan; Cheng, Shiming (Frontiers in Plant Science, 2026)
Rubus chingii Hu. is a versatile plant valued for its medicinal and edible properties. Its fruits are rich in flavonoids, with unripe fruits exhibiting higher flavonoid content. This study identified the WRKY gene family in this plant and explored its regulatory mechanisms in flavonoid synthesis. In total, 52 members of the RcWRKY family were identified; they were unevenly distributed on six chromosomes and all located in the nucleus. Based on the phylogenetic tree, these 52 members were divided into seven subgroups, and the motifs and gene structures of different subgroups were highly consistent. Their promoters were rich in elements such as light and jasmonic acid methyl response elements. Additionally, 20 collinear gene pairs were identified in the genome, most of which underwent purifying selection. Whole-genome duplication was the main cause of expansion of the RcWRKY family, and most members showed obvious collinearity with dicotyledonous plants. Transcriptome analysis revealed that 47 RcWRKY members were differentially expressed during fruit ripening, and 11 were highly expressed at the mature green (MG) stage with high flavonoid content. Additionally, the 30 identified flavonoid synthesis-related genes were highly expressed in the MG period, with six RcWRKY members being significantly positively correlated with most flavonoid synthesis genes. Reverse transcription-quantitative polymerase chain reaction and subcellular localization confirmed that RcWRKY34 and RcWRKY37 were highly expressed in the MG period and located in the nucleus. Dual-luciferase assay showed that both RcWRKY34 and RcWRKY37 positively regulated the flavonoid synthesis gene LG07.48. Overall, this study lays a foundation for enhancing the medicinal value of palm-leaved R. chingii.